The Effectiveness of Digital Marketing and Pricing on Generation Z's Purchasing Decisions on TikTok Shop by Tokopedia - Hamonongan, Daniel Satrio; Patimah, Siti; Pragiwani, Meita (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2026)
This research examines the influence of digital marketing and price on the purchasing decisions of Generation Z users of TikTok Shop by Tokopedia among students of SMK ICB CN Bandung. The study aims to analyze the effects of digital marketing and price, both partially and simultaneously, on purchasing decisions. A quantitative approach with an ex post facto method was employed. The population consisted of students who actively use TikTok Shop by Tokopedia. Using purposive sampling, 190 respondents were selected based on the Hair formula. Primary data were collected through structured questionnaires and analyzed using statistical techniques. The findings indicate that digital marketing, price, and purchasing decision variables are generally in the good category. Digital marketing has a positive and significant effect on purchasing decisions. Price also has a positive and significant effect and exerts a stronger influence than digital marketing. Simultaneously, both variables significantly affect purchasing decisions. Although challenges such as information accuracy and perceived price value were identified, the overall implementation of digital marketing and pricing strategies supports Generation Z consumers in making purchasing decisions through TikTok Shop by Tokopedia. These findings highlight the importance of effective digital marketing and competitive pricing in influencing online purchasing behavior.